“We have same background” as Japan’s propaganda to Indonesia - Rosalini, Raisa Hashina (Advances in Social Sciences Research Journal, 2022)
This paper analyzes how propaganda works during the war, focusing on Japanese propaganda during its occupation in Indonesia between 1943-1945 through the magazine. Using the text analysis approach, this paper tent to analyze how Djawa Baroe magazine, which consists of 250 articles, works as a propaganda tool in doctrine and mobilizes its dominated society. The research was conducted through three stages of analysis and later analyzed through critical discourse analysis. It can be seen that Japan uses Djawa Baroe magazine as a propaganda tool by showing a variety of persuasion, doctrine, proximity aspect, and the implementation of Japanese cultural influences in Indonesian society. In conclusion, the propaganda strategy used by Japan during its occupation in Indonesia can be seen from the style of language, the article’s content, the use of provocative or persuasion sentences and images, and the information displayed in articles.